Towards a sustainable future for Nunavik. (July 2014) - Rodon, Thierry; Schott, Stephan
ABSTRACT The predominantly Inuit Arctic region of Nunavik in the Province of Québec, Canada, currently needs to address major challenges and opportunities. The region needs to develop more employment and wealth creation opportunities without sacrificing the vital land-based subsistence sector that provides food security, sustains cultural identity and provides social and economic stability. A decision about a new direction needs to be taken soon as major mining projects are developing at a rapid pace. In this paper we first assess existing socioeconomic and living conditions data to evaluate the state of social well-being in the region. In addition we report and analyse information from an economic forum in Kuujjuaq, Nunavik in April 2010. The purpose of the forum was to provide an opportunity for regional and local stakeholders to obtain information on specific economic opportunities for Nunavik and to discuss their merit for the communities. Based on our data evaluation and the outcomes at the forum we identify a possible sustainable development feedback envisioning process and discuss possible sustainable development directions for Nunavik.